2001
DOI: 10.1038/sj.bjp.0704293
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid CB1‐receptor mediated regulation of gastrointestinal motility in mice in a model of intestinal inflammation

Abstract: 1 We have studied the eect of cannabinoid agonists (CP 55,940 and cannabinol) on intestinal motility in a model of intestinal in¯ammation (induced by oral croton oil in mice) and measured cannabinoid receptor expression, endocannabinoids (anandamide and 2-arachidonylglycerol) and anandamide amidohydrolase activity both in physiological and pathophysiological states. 2 CP 55,940 (0.03 ± 10 nmol mouse 71) and cannabinol (10 ± 3000 nmol mouse 71 ) were more active in delaying intestinal motility in croton oil-tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
214
2
4

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 234 publications
(240 citation statements)
references
References 45 publications
11
214
2
4
Order By: Relevance
“…In another study of LPS-induced inflammation, the FAAH inhibitor AM3506 normalized hypermotility in a CB 1 -and CB 2 -dependent manner, whereas colonic propulsion was CB 1 -dependent [21]. Interestingly, the effect of cannabinoids in cases of inflammatory hypermotility occurred at lower doses than in control states [8,22]. This could be due to the increased receptor expression during inflammation, to increased coupling of the receptor to effectors proteins, or both.…”
Section: Role Of the Ecs In Gut Homeostasismentioning
confidence: 97%
See 3 more Smart Citations
“…In another study of LPS-induced inflammation, the FAAH inhibitor AM3506 normalized hypermotility in a CB 1 -and CB 2 -dependent manner, whereas colonic propulsion was CB 1 -dependent [21]. Interestingly, the effect of cannabinoids in cases of inflammatory hypermotility occurred at lower doses than in control states [8,22]. This could be due to the increased receptor expression during inflammation, to increased coupling of the receptor to effectors proteins, or both.…”
Section: Role Of the Ecs In Gut Homeostasismentioning
confidence: 97%
“…Under normal conditions, CB 1 mediates the effects of cannabinoids on motility; however, in inflammatory states both CB 1 and CB 2 receptor activation may reduce inflammation-induced hypermotility. For instance, in lipopolysaccharide (LPS)-induced intestinal inflammation, hypermotility was normalized following CB 2 (but not CB 1 ) activation [19,20], whereas in croton oil-induced hypermotility CB 2 antagonism did not reverse the effect of the cannabinoid agonist CP55,940 [8]. In another study of LPS-induced inflammation, the FAAH inhibitor AM3506 normalized hypermotility in a CB 1 -and CB 2 -dependent manner, whereas colonic propulsion was CB 1 -dependent [21].…”
Section: Role Of the Ecs In Gut Homeostasismentioning
confidence: 99%
See 2 more Smart Citations
“…77 Pharmacological studies have demonstrated that anandamide and various CB 1 agonists inhibit gastrointestinal motility in rodens in vivo and in isolated ileum and colon from both animals and humans. 20,80,81 In clinical trials with rimonabant for nicotine cessation or obesity, it was seen that incidence of diarrhea was higher in patients receiving rimonabant than with placebo. Therefore this suggests that blocking CB 1 receptors accelerated gastrointestinal transit and secretions 20 , so CB 1 agonists may prove useful in diarrhea-predominant IBS while CB 1 antagonists can help in constipation-predominant IBS.…”
Section: Irritable Bowel Syndrome (Ibs)mentioning
confidence: 99%